Total rehabilitation with implant-supported and implant-retained prostheses in atrophic maxillae: Aesthetic and functional resolution for totally edentulous patients (Research, Society and Development, 2022)
Introduction: Implant-supported prostheses are an excellent treatment option for totally edentulous patients, however, some conditions, such as extremely atrophic jaws, may limit their application. Aims: to demonstrate and discuss, through a series of clinical cases, the functional aesthetic resolution of totally edentulous patients with atrophic maxillae, using three different implant-prosthesis approach. Methods and Material: This article describes a clinical case series of patients has between 65 and 75 years old, who lost all upper teeth and had severely atrophic jaws. Due to the bone situation of the maxilla, an osteotome was planned for sinus floor elevation and followed by an allogeneic bone graft. After 18 months of bone integration, osseointegrated implants were installed and different prostheses were made for each case. Conclusions: It is possible to conclude that with the use of advanced surgical and prosthetic planning it is possible to recover the aesthetics and function of a serious and complex clinical case.